INFLUENCE OF PRICE TO DECISION OF PURCHASE OF SOSRO BOTTLE TEA DRINK AT PT. RAYS SOSRO BRANCH PEKANBARU - Fitri, Zefno; Oji Salmayanti.Z, Dara Aguslin (Eko dan Bisnis: Riau Economic and Business Review, 2019)
Increasing business competition in the beverage industry makes the company do the right marketing strategy so that its business can survive and win the competition. The more competitors the more choices for customers to be able to choose products that fit their expectations, so the consequence is the company should pay more attention to the quality and price of its products in order to become the appeal of consumers to buy the product. Tea bottle sosro as market leader in IndonesianÂ  decreased market share due to the arrival of competitors. drink tea This study aims to determine the effect of price on purchasing decisions on sosro bottled tea drink in Pekanbaru. The data used in this study are primary data (data obtained directly from respondents) and secondary data (data obtained indirectly). The object of research that becomes independent variable is price (X) and purchasing decision (Y) as dependent variable. Population in this research is consumer of PT. Sinar Sosro Pekanbaru, which amounted to 9,324 people in 2017. Sampling in this study using simple random sampling method using slovin formula, so that the results obtained 99 samples. Instrument test is done with validity test and reliability test and analysis technique used is regression linear analysis and software SPSS. The result of the research shows that the influence of price on the decision of purchasing bottle drink of Pekanbaru sosro bottle of R2 = 0.110 or 11%, influencing the purchasing decision variable (Y). The conclusion of this study is that price has a positive result on purchasing decision. While the rest can be explained by other variables variables not examined in this study. Feom the results of this study it is recommended for at PT RAYS SOSRO consider more in setting affordable prices for consumers of ready to drink tea